A pilot and feasibility study of the effectiveness of care mapping on person-centred care in neurorehabilitation settings. Issue 9 (20th October 2020) - Brown, Laura J. E.; Blake, Daniel; Berry, Katherine; Sheldrick, Russell
ABSTRACT: Dementia care mapping for neurorehabilitation (DCM-NR) is a tool designed to increase person-centred care (PCC) in neurorehabilitation settings. This paper reports pilot and feasibility testing of a cluster-randomized controlled trial assessing the effectiveness of DCM-NR at increasing PCC. Forty-one staff members, from four neurorehabilitation wards, were cluster-randomized to receive DCM-NR (experimental group) or care as usual (control). Measures of PCC, attitudes to people with brain injury, and PCC self-efficacy were taken at baseline and follow-up. The experimental group were also interviewed about their experiences of the trial. Twenty-nine participants completed the study. Participants generally found the intervention and trial to be acceptable. PCC was significantly higher in the experimental than the control group at follow-up, despite levels of exposure to the intervention being low. PCC self-efficacy increased in the control group, but not in the experimental group, perhaps reflecting an initial reduction in perceived competence following feedback. Neither group showed a change in attitudes to people with brain injury. The findings suggest that this cluster-randomized trial design is acceptable; that DCM-NR shows promise as a tool for increasing PCC; and highlight modifications to the protocol that could increase the success and theoretical value of a future large-scale study.